Urban Green Space Development StrategyâReconverting Gas Station To Public Parks In The City Of Surabaya, Indonesia - Hasyimi, Valid; Suroso, Djoko Santoso Abi (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Urban Green Space Development has become a challenging task for city governments especially in Indonesia, due to high prices of land around urban centers. On the other hand, there are inconsistencies between land use and land allocation within the city planning. In Surabaya City, quite a lot of gas stations were built on areas which are originally intended for green open spaces. Surabaya City Municipality is strongly committed to reconvert Gas Station Areas to green open spaces as determined in the plan. Innovative strategies have enabled the city government to reconvert 13 gas stations to public parks. This paper analyzes the implementation process of the Urban Green Space Reconversion Policy, describing the historical details of the issues, the  taking over of land from gas station owners, and the park development and campaigning. Discussion also includes the most influential factors in this success story.